ANALYSIS OF OLIVIA PULLMAN’S CHARACTER IN “WONDER” MOVIE - Mukhlasul Fasikh; Yessy Indriana (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2022)
In this research the author used Sigmund Freud's psychoanalytic theory which discusses a person's behavioral personality and Suseno's moral theory. The main discussion in this research is to focus on the personality of the Id, Ego and Superego as well as the moral values contained in the characterization of Olivia Pullman. The purpose of this research is to describe the character of Olivia Pullman in terms of literary psychology and to describe the moral values contained in the characterization of Olivia Pullman. The method used in this research is a qualitative descriptive method in the form of excerpts of dialogues between characters in the movie. The results of the analysis show that the superego personality is more dominant because Olivia Pullman's character is not only concerned with her own desires but also cares about the feelings of others. Therefore, the moral value that is more dominant in the characterization of Olivia Pullman is the moral value of independence which is shown through Olivia Pullman's daily life who is always alone because her best friend left her and lack of attention from her parents.